Black Gold - Henry, Marguerite, 1902-1997.; Dennis, Wesley (New York : Aladdin Books, 1992)
A heroic small-boned horse with a will to win is finally ridden to glory by his devoted jockey.
5.2
3-6
Keywords: Horses -- Juvenile fiction; Horse racing -- Fiction; Horses -- Fiction; Horse racing -- Fiction; Horses -- Fiction